Reconstruction of Criminal Law Policy in Tackling Digital-Based Crime in the Era of Artificial Intelligence - Suwarto, Suwarto; Sutiarnoto, Sutiarnoto; Magda, Marianne (Ipso Jure, 2026)
The development of digital technology characterized by the use of artificial intelligence has given birth to new forms of crime that are complex, anonymous, and cross-border, thus challenging the conventional construction of criminal law. The character of digital-based crime shows a fundamental shift from physical crime to system, data, and algorithm-based crime, which has not been fully accommodated in Indonesia's criminal law policy. This research aims to analyze the construction of criminal law policy in tackling digital-based crime in the era of artificial intelligence and formulate the idea of adaptive and fair criminal law policy reconstruction. The research method used is normative juridical with a statutory and conceptual approach, through an analysis of Law Number 1 of 2024 concerning the Second Amendment to the Law on Information and Electronic Transactions and Law Number 1 of 2023 concerning the Criminal Code. The results of the study show that criminal law policy is still reactive, fragmentary, and dominated by the classical paradigm, thus causing problems in the formulation of delicacies, criminal liability, and proof of crimes based on artificial intelligence. Criminal law policy reconstruction is needed through paradigm reform, harmonization of norms, strengthening the criminal accountability model, and integrating penal and non-penal policies to ensure legal certainty, community protection, and justice in the digital era.